(untitled) (The Journal of Psychology and Sociology, 2017)
Homelessness is a social problem which exists in different scales in all contemporary societies. Fighting against homelessness requires a broad understanding, which would give an idea of the ways and the processes leading to it. This article is devoted to understand who are homeless people. In order to achieve this goal we can consider three issues: the definition of homelessness, the causes of homelessness and European typology of homelessness, and housing exclusion. As a result the following definitions were formulated: Homelessness - it is a social and legal status, a social phenomena and a problem, which are characterized by individual’s or social group’s absence of right, place or social opportunities for adequate to human needs housing and therefore who has a right to receive special services. Homeless person - an individual who does not have right, location or social opportunities for adequate to human needs housing and therefore who has a right to receive special services. Homeless people - a social group of homeless individuals. The causes of homelessness can be divided into three groups: structural, system failures, and individual circumstances. In other words, the causes of homelessness can come at the level of the social structure, at the level of organization and at individual or primary social group levels. For example, structural factors are poverty and high housing prices. System failures include a lack of coordination or ineffectiveness of services for the provision of housing in vulnerable people support systems. The individual causes are accidents (e.g., fire), fraud, problems in family relations (divorce, quarrel with parents), problems in family (e.g., when a family member has a gambling addiction). The article also examined the European typology of homelessness and exclusion from the house, which identifies 13 groups of homeless people on the basis of the housing situation. It is based on the assumption that there are three features that make the concept of «home» - the right to housing, social conditions. The absence of one trait can lead to homelessness. Key words: homelessness, homeless people, European typology of homelessness and house exclusion.